Colorectal Cancer in Patients Younger than 40 years -Analysis of Clinicopathological Profile and Treatment Pattern - PS, Amogh; Narayanan, Geeta S; B, Sai Sanmathi; BR, Kiran Kumar (Asian Pacific Journal of Cancer Biology, 2024)
Background: The incidence of colorectal cancer (CRC) is increasing among young adults. Cancer diagnosis in young adults leads to many challenges due to the impact of the disease on their fertility, career, and life expectancy. In the present study, we investigated the clinicopathological profile of colorectal cancer patients younger than 40 years. Materials and Methods: Retrospective analysis of all the biopsy proven CRC patients were collected over the period of 5 years, from January 2012 to December 2018. Clinicopathological data of patients under the age of 40 years were collected from their medical and pathological reports and analysed. Results: Out of 729 CRC, a total of 154 (21%) patients of colorectal cancer were younger than 40 years were registered during the study period. Among them, with 94 (61%) being male and 60 females (39%). Most of the patients were 30-35 years (37%) and less than 30 years (36%) age group. Adenocarcinoma was present in 97% patients and signet ring cell carcinoma in 3% patients The most common primary site was rectum (57 %), followed by ascending colon (17 %). Most of the patients presented with stage III (64 %) disease. The liver was the most common site of distant metastasis. Conclusion: The incidence of colorectal cancer is increasing among young adults. Most patients present in a locally advanced and non-metastatic stage and have the potential for curative treatment. Therefore, early detection by screening at a younger age may improve the survival of younger patients. Long term follow-up of these patients will provide insights on Treatment Outcomes.